2015
DOI: 10.3109/0284186x.2015.1061212
|View full text |Cite
|
Sign up to set email alerts
|

A simulation study on proton computed tomography (CT) stopping power accuracy using dual energy CT scans as benchmark

Abstract: Background. Accurate stopping power estimation is crucial for treatment planning in proton therapy, and the uncertainties in stopping power are currently the largest contributor to the employed dose margins. Dual energy x-ray computed tomography (CT) (clinically available) and proton CT (in development) have both been proposed as methods for obtaining patient stopping power maps. The purpose of this work was to assess the accuracy of proton CT using dual energy CT scans of phantoms to establish reference accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 26 publications
6
76
0
Order By: Relevance
“…The estimated range uncertainty (2 σ ) was approximately 2.2% for three tumor sites, as compared with the 1% uncertainty reported in previous studies (Hünemohr et al , 2014; Bourque et al , 2014; Hansen et al , 2015). The major difference between our study and others is that CT number variation due to the beam hardening effect was previously avoided by using the same scanning condition, upon calibration and real measurements.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The estimated range uncertainty (2 σ ) was approximately 2.2% for three tumor sites, as compared with the 1% uncertainty reported in previous studies (Hünemohr et al , 2014; Bourque et al , 2014; Hansen et al , 2015). The major difference between our study and others is that CT number variation due to the beam hardening effect was previously avoided by using the same scanning condition, upon calibration and real measurements.…”
Section: Discussionsupporting
confidence: 67%
“…This result indicated that the calculation algorithm can be designed more robustly against CT number variation. New algorithms have recently been proposed (Hansen et al , 2015; Han et al , 2016; Taasti et al , 2016) and will be included for comparison purposes in our future work. Note that these findings might not be directly transferrable to real human tissues, due to the study being based on tissue surrogate phantoms and theoretical human tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those methods that use a calibration phantom with known ρ e and Z eff are of special practical interest because they do not require prior knowledge of the CT scanner spectra, which are not always readily available. Hansen et al . presented an SPR estimation scheme for proton therapy treatment planning by combining the calibration‐based methods of Saito for ρ e calculation and of Landry et al .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is worth discussing the recent interest in dual energy CT (DECT) estimation of SPR, which has been reported to be superior to conventional, single energy CT conversion . Recently in‐room CT scanners with DECT capability have become available, and several centers are now equipped with the technology .…”
Section: Beyond Anatomy‐based Positioningmentioning
confidence: 99%